2018
DOI: 10.1016/j.margeo.2018.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus dynamics around the sulphate-methane transition in continental margin sediments: Authigenic apatite and Fe(II) phosphates

Abstract: The formation of authigenic phosphate minerals in marine sediments is an important process for the burial and long-term storage of the bio-essential nutrient phosphorus (P). In this context, we report the composition of pore waters, bulk sediments, and the speciation of P in four sediment cores recovered on the continental margins off the Amazon, Rio de la Plata and Zambezi rivers. Here, pronounced sulphate-methane transitions (SMTs) occur between 4.5 and 6.5 m sediment depth where sulphate is consumed by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 100 publications
1
42
0
Order By: Relevance
“…Again, the only departure is associated with the coarser layer deposited during the Last Glacial Maximum, which yields atypically old radiocarbon ages relative to the surrounding sediment. These observations are consistent with increased slumping and/or turbidity currents (e.g., Zhong et al, 2015) driven by gas hydrate destabilization on the upper continental slope, and concomitant continental-slope failure during sea-level low stands (Kennett et al, 2003;Maslin et al, 2004).…”
Section: Geological Background and Study Sitesupporting
confidence: 76%
“…Again, the only departure is associated with the coarser layer deposited during the Last Glacial Maximum, which yields atypically old radiocarbon ages relative to the surrounding sediment. These observations are consistent with increased slumping and/or turbidity currents (e.g., Zhong et al, 2015) driven by gas hydrate destabilization on the upper continental slope, and concomitant continental-slope failure during sea-level low stands (Kennett et al, 2003;Maslin et al, 2004).…”
Section: Geological Background and Study Sitesupporting
confidence: 76%
“…2d). Methanotrophs, such as ANMEs, were found to be involved in iron-coupled AOM in marine and freshwater cultures (Scheller et al, 2016;McGlynn et al, 2015;Ettwig et al, 2016;Cai et al, 2018). ANMEs were found here with relatively low frequencies (ANME1, below 1 % in most samples, circa 5 % in the 185 cm layer), and their role in iron reduction within the SE Mediterranean sediments remains to be tested.…”
Section: Potential Microbial Playersmentioning
confidence: 83%
“…These environments are typically characterized by high sedimentation rates and/or high loading of iron oxides, facilitating the burial of reactive iron oxides beneath the SMT. Such environments bearing elevated dissolved iron concentrations as indicator for ongoing iron reduction are widely distributed from shallow sediments on coastal shelves to deep sub-seafloor settings at lower continental margins (Figure 1; Aller et al, 1986;Schulz et al, 1994;Kasten et al, 1998;Hensen et al, 2003;D' Hondt et al, 2004;März et al, 2008März et al, , 2018Fulthorpe et al, 2011;Holmkvist et al, 2011;Lim et al, 2011;Takahashi et al, 2011;Riedinger et al, 2014;Treude et al, 2014;Egger et al, 2015Egger et al, , 2016aEgger et al, ,b, 2017Oni et al, 2015;Rooze et al, 2016). Besides, Fe-AOM might have been an important methane sink in the early Archean before the accumulation of sulfate in the ocean (Konhauser et al, 2005) and it was previously suggested that Fe-AOM should be considered in methane oxidation estimates from marine environments (Riedinger et al, 2014).…”
Section: Environmental Significance Of Fe-aom In Marine Sedimentsmentioning
confidence: 99%